Properties of the Loess Sediments in Ostrava Region (Czech Republic) and Comparison with Some Other Loess Sediments - Marian Marschalko; Işık Yilmaz; Lucie Fojtova; David Lamich; Martin Bednarik (The Scientific World Journal)
This study deals with a methodical identification and evaluation of physical-mechanical properties of one genetic type of geological structure. This is represented by an engineering-geological zone of eolian sediments, which is regionally rather abundant. The paper contributes to a need to identify typical soil properties for widespread geological environments in a particular region and thus add to good engineering geologists and geotechnical engineers’ awareness in the region. Such information is much required as it permits comparing results of newly conducted engineering-geological investigations and research with the results characteristic for the region in question. It is vital for engineering geologists and geotechnical engineers to be sufficiently informed on the foundation soil properties of widespread geological environments because of professionalism and higher quality of their work results. Comparing other loess sediment studies worldwide it was discovered that the physical properties of the most abundant clays of low to medium plasticity, sandy clays, and sands as foundation soils vary as for the plasticity index, porosity, natural water content, and bulk density to a certain extent but not as significantly as once expected.